Wordwall Media and its Impact on Understanding Light Material in Class V Elementary School Science Subjects - Dexani Widyasari; Woro Sri Hastuti; Supartinah Supartinah; Anwar Senen (Postgraduate, University of Mataram, 2024)
Using technology for learning is really important. This research wants to see if using word wall media helps 5th-grade students understand light in science class. This research method is quantitative experimental quasi experimental design type Post-test only control group design. The sampling technique is purposive sampling. The results of this research show the influence of the use of wordwall media on the understanding of light at Benerwetan State Elementary School and Kaibon State Elementary School. The normality test showed that the experimental class had a significance of 0.15 and the control class had a significance of 0.15, both greater than 0. 05 The homogeneity test showed a p-value of 0.47, which is higher than 0.05, and the hypothesis test showed a p-value of 0. 000, which is lower than 0. 05, so it can be concluded that there is an